PENGENALAN WAJAH DENGAN BANYAK POSISI (MANY POSITIONS) MENGGUNAKAN ALGORITMA FISHER LINEAR DISCRIMINANT (FLD) - Mulyadi (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2020)
The face is one of the characteristics that can determine a person's identity, because each individual has a different face. Face recognition technology is highly developed today, which has been widely used systems based on face recognition. The main issue that arises is change in the position where it will affect the system in detecting the presence of a face which will also affect the system at the next stage of face recognition. Based on this background, it created a system that is able to recognize a person's identity in the form of a face name is entered with a variety of positions. In this research method used is Fisher Linear Discriminant (FLD). FLD can be used to recognize faces with a variety of positions. This study was able to detect and recognize faces with five different positions. The position of the recognized ie perpendicular to the position of 0 °, 1-25 ° turn to the right, looked left 1-25 °, 1-25 ° 1-25 ° looked up and down with the distances are 50 cm, 60 cm, 70 cm, 80 cm, 90 cm and 100 cm. In this test, the face image is tested by 300 overall face to face data 254 works and 46 face data were not successful. From these data, then get the success percentage of 84.67%.